Manajemen Risiko Produksi Akuaponik di PT Tanikota Agribudaya Edulestari - Ifdal, Muhammad Khairy; Supyandi, Dika (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Aquaponic production results at PT Tanikota Agribudaya Edulestari (TABEL)  has not met the standards desired by the company. This is shown by the results of aquaponic vegetable and fish production which are still experiencing fluctuations. This fluctuation in production results is related to the risks that occur during the aquaponics production process. This research is qualitative and adopts a case study approach. The analysis method used is House of risk (HOR). This method involves HOR stage 1 to identify risk events and risk sources, as well as HOR stage 2 to formulate management strategies. The aim of this research is to find out what risks and sources of risk faced by PT TABEL and develop mitigation strategies to manage these risks. Based on the research results, it was found that there were 23 risk events caused by 22 risk sources in the aquaponics production process at PT TABEL. Based on the 22 risk sources identified, 8 priority risk sources were obtained, namely worker imbalance, frog-eye leaf spot disease, caterpillar pests, root rot disease, cleanliness of the place, rainy season, plants are not exposed to sunlight, and problematic fish seeds. In managing these sources of risk, 8 management action strategies have been determined which have been sorted based on implementation priorities, namely conducting routine evaluation and monitoring organized and digitalized production scheduling and record keeping, making pest traps, using biological control, arranging and rotating crops that are not exposed to sunlight, create a separate place for post-harvest activities, optimize the use of waring in roder tents, and improve good communication with fish seed suppliers.